Precious Insights into Knowledge, Ethics, and Household Expenditures: A Critical Edition of the Selected Excerpts from Kitāb al-Mawāhib al-ʿAliyyah fī al-Jamʿi Bayn al-Ḥikam al-Qur’āniyyah wa al-Ḥadīthiyyah (Book of the Exalted Gifts in the Integration of Qur’anic and Hadith Wisdom) - Akbar, Mohamed Aslam (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
Kitāb al-Mawāhib of Alī al-Muttaqī (Book of Wisdom) is a compendium of one thousand pieces of wisdom from Holy Qur’ān and Ḥadīth. Among the early scholarships in the collections of wisdom, al-Muttaqī’s book is one of the most excellent compilations ever made. A critical edition of this work provides an in-depth study of selected excerpts from the manuscript, focusing on the themes of knowledge, ethics, and household expenditures, presenting insights into the author's unique categorization and organization of this wisdom. It offers an enhanced understanding of the integration of Qur’anic and Ḥadīth wisdom, revealing valuable lessons and historical insights that remain relevant to contemporary readers, scholars, and researchers interested in Islamic thought and civilization.